India's Rise: Becoming a New Economic Power in the Era of Globalization - Sapitri, Dian (Jurnal Indonesia Sosial Sains, 2025)
India’s rapid economic rise, fueled by its demographic dividend and post-1991 liberalization, positions it as a future global power. However, challenges like inequality and skill gaps persist. This study examines India’s economic potential by 2030, analyzing demographic trends, sectoral shifts (IT, manufacturing, renewables), and policy impacts. A literature review synthesizes data from World Bank (2025), ESCAP (2022), and case studies (e.g., Bangalore’s tech hubs), employing qualitative analysis of GDP projections, workforce demographics, and foreign investment trends. India’s productive-age population (15–64 years) will peak by 2030, supporting GDP growth of 6–8% annually. The IT and pharmaceutical sectors dominate exports, while AI and renewables emerge as new frontiers. However, rural-urban inequality and infrastructure deficits threaten inclusive growth. Policymakers must prioritize education and rural development to harness demographic potential. For global stakeholders, India’s low-cost, high-skilled workforce offers competitive advantages in services and technology. This research underscores India’s transition from regional player to global economic leader, contingent on addressing structural disparities.